O efeito do tratamento com o levosimendan sobre um modelo de hipertensão arterial sistêmica em ratas idosas espontaneamente hipertensas - PIRES, Flávio de Oliveira (2021)
Introduction: Levosimendan (LEV) is an inodilator capable of increasing the contractility of the heart muscle and relaxing coronary vessels. Objective: To verify whether chronic treatment with LEV in a model of systemic arterial hypertension in spontaneously hypertensive elderly rats (SHR) will cause reduced blood pressure, improvement in autonomic function and simpatovagal balance in animals treated with this drug for 30 and 60 days. Methods: Thirty-six elderly rats aged 2 years from 2 strains, one group consisting of Wistar (n = 10), 26 spontaneously hypertensive rats (SHR), divided into three groups: SHR control without treatment (n = 10), group treated with LEV for 30 days (LEV 30 D) (n: 8) and the group treated with LEV for 60 days (LV 60 D) (n: 8) with daily doses of 0.05 μg / kg administered by oral gavage. LEV doses were calculated according to the body weight of the animal in the week before dosage. Plethysmography (indirect method of blood pressure assessment), hemodynamic measurements, variability of blood pressure and pulse interval, symbolic analysis, weights of animals and total and relative body tissues, analysis and counting of inflammatory cells of the liver and heart were evaluated, and the percentage of collagen present in the heart after LEV intervention was evaluated. Results: When compared with the SHR control group, the LEV 60 D group presented a decrease in the total body mass of the heart (p < 0.05) and of the total body mass of the left ventricle (p < 0.05). Regarding plethysmography, when compared to the SHR control group, the LEV 30 D and 60 D groups presented a decrease in systolic blood pressure (p < 0.05) on the 30th day of evaluation. On the 45th and 60th days of evaluation, there was a decrease in systolic blood pressure in the LEV 60 D group compared to the SHR control group (p < 0.05). As for diastolic blood pressure, there was a decrease in diastolic blood pressure in the LEV 30 D group compared to the SHR control group on the 15th day (p < 0.05) and in both the LEV 30 D and LEV 60 D groups compared to the SHR group control (p < 0.05) on the 30th day of evaluation. Still evaluating the diastolic blood pressure on the 45th and 60th days, there was a decrease in systolic blood pressure in the LEV 60 D group compared to the SHR control group (p < 0.05). In the analysis of the behaviour of cardiac autonomic modulation in frequency and time domain and symbolic analysis, there was a decrease in systolic blood pressure in the LEV 60 D group compared to the control SHR group (p < 0.05), an increase in RMSSD in the LEV 60 group D compared to the SHR control group (p < 0.05) and increased parasympathetic modulation in absolute values (p < 0.05). In percentage values when comparing the SHR group with the LEV 60 D group, there was a decrease in sympathetic modulation (LF) (p < 0.05) and the balance of the rate of sympathetic and parasympathetic modulation defined by the ratio (LF/HF) (p<0.05), as well as, increased parasympathetic modulation (HF) (p<0.05). In the analysis of the variability of systolic blood pressure in the time and frequency domain, when comparing the SHR control group with the LEV 60 D group, an increase in parasympathetic modulation (2UV) was observed in the LEV 60 D group (p < 0.05). There was also a decrease in enddiastolic pressure in the LEV 60 D group compared to the SHR control group (p < 0.05). Regarding the bradycardic response rates, there was an increase in the groups treated with LEV compared to the SHR control group (p < 0.05) and regarding the tachycardic response rates, there was also an increase in the groups treated with LEV compared to the SHR control group (p<0.05). Regarding the percentage of collagen in the heart, there was a decrease in the LEV groups compared to the control SHR (p <0.05). Conclusion: Chronic treatment with LEV in a SHR elderly rats promoted acts not only improving cardiac contractility but also autonomic modulation of heart rate and promoting the drop in blood pressure in the old rats.